2017
DOI: 10.1371/journal.ppat.1006630
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ extends the immune functions of Guanylate Binding Proteins to inflammasome-independent antibacterial activities during Francisella novicida infection

Abstract: Guanylate binding proteins (GBPs) are interferon-inducible proteins involved in the cell-intrinsic immunity against numerous intracellular pathogens. The molecular mechanisms underlying the potent antibacterial activity of GBPs are still unclear. GBPs have been functionally linked to the NLRP3, the AIM2 and the caspase-11 inflammasomes. Two opposing models are currently proposed to explain the GBPs-inflammasome link: i) GBPs would target intracellular bacteria or bacteria-containing vacuoles to increase cytoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 65 publications
3
63
0
Order By: Relevance
“…Tularemia vaccination also induced changes in 23 early signatures that were not seen after other vaccines, including greater induction of members of the GBP family that are known to be induced by IFN-γ [30] and have been linked with control of Francisella infection in mice [31]. Although several interferon-inducible genes were associated with YF-17D, LAIV, and TIV, upregulation of GBPs was unique to tularemia.…”
Section: Discussionmentioning
confidence: 94%
“…Tularemia vaccination also induced changes in 23 early signatures that were not seen after other vaccines, including greater induction of members of the GBP family that are known to be induced by IFN-γ [30] and have been linked with control of Francisella infection in mice [31]. Although several interferon-inducible genes were associated with YF-17D, LAIV, and TIV, upregulation of GBPs was unique to tularemia.…”
Section: Discussionmentioning
confidence: 94%
“…More specifically, mGBPs regulate programmed cell death pathways involving caspases 3, 8, and 9. 45 The same group also showed that, contrary to the mouse caspase-11, the human homologue caspase-4 is able to detect cytosolic tetra-acylated LPS that has been released from F. novicida. Interestingly, hGBP2 contributes to the activation of the caspase-4 noncanonical inflammasome in human macrophages upon F. novicida infection, 46 similarly to what has been observed for mGBP2 in promoting caspase-11 activation in response to L. pneumophila infection.…”
Section: Gbps In the Defense Against Intracellular Bacteriamentioning
confidence: 99%
“…It was recently shown that mGBPs also contribute for AIM2‐independent cell death upon F. novicida infection. More specifically, mGBPs regulate programmed cell death pathways involving caspases 3, 8, and 9 . The same group also showed that, contrary to the mouse caspase‐11, the human homologue caspase‐4 is able to detect cytosolic tetra‐acylated LPS that has been released from F. novicida .…”
Section: Introductionmentioning
confidence: 99%
“…GBPs are a family of dynamin-related large GTPases that are expressed in response to IFNs and other proinflammatory cytokines to mediate a broad range of pathogen-induced innate immune responses (41). In immune cells, GBPs activate NLRP3 and AIM2 inflammasomes in conjunction with bacterial signals to induce pyroptosis (42)(43)(44)(45)(46)(47). Together, these data suggest that another potential mechanism of enhanced NETosis in risk neutrophils is via IFN signaling because IFNs are reported to prime neutrophils for NETosis (38,(48)(49)(50).…”
Section: Resultsmentioning
confidence: 99%